Addressing learner anxiety via reflective practice. (25th October 2021) - Siden, Jonathan Y.; Murphy, Jennifer; Wolff, Meg
Abstract: Background: Medical students experience anxiety when learning the pelvic, breast and male genitourinary exam (also known as sensitive physical exams). Reflection can help students process emotionally challenging learning experiences and help give those experiences meaning. We describe the development of a reflection module to enhance reflection during sensitive exam instruction. Approach: We developed this module following Kern's Six Step Method for curriculum development, including a targeted needs assessment. Informed by educational reflection theory, the module addressed all elements of reflection. The module was optional, asynchronous and administered online, requiring minimal administrative support. Prior to sensitive exam instruction, participants identified goals and values and named emotions. Following exam instruction, participants again named their emotions and then self‐evaluated whether they had met their goals and upheld their values. Evaluation: Participants found the module to be a useful modality to reflect. Most notably, they identified the naming of emotions, goals and values clarification and the opportunity to reflect both prior to and after an educational experience as helpful. Younger students found the module particularly helpful. Implications: An online, low‐resource, asynchronous reflection module is feasible and can be a way for students to reflect on challenging learning experiences. In addition to using with sensitive exam instruction, the module can be applied to activities such as anatomic dissection, ethics workshops or clinical learning.